2008
DOI: 10.1016/j.ypmed.2007.11.014
|View full text |Cite
|
Sign up to set email alerts
|

Early mixed feeding and breastfeeding beyond 6 months increase the risk of postnatal HIV transmission: ANRS 1201/1202 Ditrame Plus, Abidjan, Côte d'Ivoire

Abstract: HAL is a multidisciplinary open access archive for the deposit and dissemination of scientific research documents, whether they are published or not. The documents may come from teaching and research institutions in France or abroad, or from public or private research centers. L'archive ouverte pluridisciplinaire HAL, est destinée au dépôt et à la diffusion de documents scientifiques de niveau recherche, publiés ou non, émanant des établissements d'enseignement et de recherche français ou étrangers, des labora… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
40
1
2

Year Published

2009
2009
2017
2017

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 55 publications
(44 citation statements)
references
References 26 publications
1
40
1
2
Order By: Relevance
“…Our observation is consistent with those of several previous studies on the role of mixed feeding in increasing the risk of mother to child transmission of HIV infection [20]. The authors converge on the hypothesis that a mixed feeding causes damage to the intestinal wall favoring passage of virus in the blood [21].…”
Section: E N'guessan Et Al Open Journal Of Obstetrics and Gynecologysupporting
confidence: 93%
“…Our observation is consistent with those of several previous studies on the role of mixed feeding in increasing the risk of mother to child transmission of HIV infection [20]. The authors converge on the hypothesis that a mixed feeding causes damage to the intestinal wall favoring passage of virus in the blood [21].…”
Section: E N'guessan Et Al Open Journal Of Obstetrics and Gynecologysupporting
confidence: 93%
“…The present study corroborates these findings. There has been less agreement about the significance of maternal age, parity, gravidity, breast abnormalities, mode of delivery, and infant gender and birth weight [11,12]. In the present meta-analysis of the composite endpoint of HIV-1 infection or death, maternal factors of parity and breast health, and infant factors of gestational age and oral candidiasis were found to be important determinants of risk.…”
Section: Discussioncontrasting
confidence: 62%
“…These studies have identified risk associations for both maternal and infant variables [8][9][10][11][12][13][14][15][16][17]. Interpreting the combined findings from these studies has been complicated by differences in the variables considered, differences in variable definitions, and inconsistencies in the associations found.…”
Section: Introductionmentioning
confidence: 99%
“…The risk of transmission by breast milk seems to be highest with mixed feeding and breastfeeding beyond 6 months of age [40]. Whilst these findings seem to suggest that breastfeeding by an HIV-infected mother is dangerous for the non-infected infant, there is growing evidence that breastfed infants have better chances of survival and may even be protected against HIV by lactic acid bacteria in breast milk [41].…”
Section: Impact Of Infections On Nutritionmentioning
confidence: 99%